Parent participation in the neonatal intensive care unit: Predictors and relationships to neurobehavior and developmental outcomes - Pineda, Roberta; Bender, Joy; Hall, Bailey; Shabosky, Lisa; Annecca, Anna; Smith, Joan (Early human development, 2018)
To 1) define predictors of parent presence, any holding, holding in arms, and skin-to-skin care in the NICU and 2) investigate the relationships between parent participation and a) early neurobehavior and b) developmental outcomes at age 4 to 5years among preterm infants. Eighty-one preterm infants born ≤32weeks estimated gestational age were prospectively enrolled within one week of life in a level III–IV NICU. Parent (maternal and paternal) presence and holding (including holding in arms and skin-to-skin care) were tracked throughout NICU hospitalization. Neurobehavior at term equivalent age and development at 4 to 5years were determined using standardized assessments. The median number of days per week parents were documented to be present over NICU hospitalization was 4.0 (IQR=2.4–5.8) days; days held per week 2.8 (IQR=1.4–4.3) days [holding in arms days per week was 2.2 (IQR=1.2–3.2) days and parent skin-to-skin care days per week was 0.2 (IQR=0.0–0.7) days]. More parent presence was observed among mothers who were Caucasian, married, older, or employed and among those who had fewer children, familial support and provided breast milk (p<0.05). More holding was observed in infants with fewer medical interventions (p<0.05) and among those who were Caucasian, had a father who was employed, had fewer children and family support (p<0.05). More parent holding in the NICU was related to better reflex development at term age (p=0.02). More parent skin-to-skin care was related to better infant reflexes (p=0.03) and less asymmetry (p=0.04) at term and better gross motor development (p=0.02) at 4–5years. Social and medical factors appear to impact parent presence, holding, and skin-to-skin care in the NICU. Parent holding is related to better developmental outcomes, which highlights the importance of engaging families in the NICU. •In the NICU, parents were present an average of 4days/week and held their infants 2days/week.•More parent holding in the NICU was related to better neurobehavior prior to NICU discharge.•More skin-to-skin care in the NICU was related to better gross and fine motor skills at 4–5years.